Initial and long-term outcomes of Percutaneous Transluminal Angioplasty for central venous stenosis or occlusion in chronic hemodialysis patients: Analysis of 363 lesions in single center - Yuki Horita; Masanobu Namura; Masatoshi Ikeda; Hidenobu Terai; Ryusuke Kimura; Taiji Yoshida; Yohei Yakuta; Katsushi Ueyama; Leo Sakakura (Archives of Clinical Nephrology - Peertechz Publications, 2021)
The purpose of this study was to evaluate the initial and long-term outcomes of Percutaneous Transluminal Angioplasty (PTA) for central venous stenosis or occlusion in chronic hemodialysis patients. A total of 363 central venous lesions (277 stenosis and 86 occluded lesions) of 146 patients were enrolled and analyzed retrospectively; these included 130 de novo lesions and 233 restenosis lesions. The procedural success rate in our cohort was 97.0% (352/363 lesions); success rate for stenosis was significantly higher than that for occluded lesions (99.3% vs. 89.5%, P < 0.001). Complications during PTA procedures occurred in nine lesions (2.5%); however, there were no serious complications. A total of 120 stents were implanted for 111 lesions; the rate of stent placement for occluded lesions was significantly higher than that for stenosis lesions (68.8% vs. 18.4%, P < 0.001).  The primary patency of de novo lesions was significantly higher than that of restenosis lesions (P = 0.0004); the assisted patency of de novo lesions at 12 and 36 months were 94.4% and 89.0%, respectively. There was no significant difference of primary patency between balloon angioplasty and stent placement for de novo lesions, however, primary patency after stent placement for restenosis lesions was significantly higher than that after balloon angioplasty (P = 0.001). In conclusion, PTA for central venous stenosis or occlusion was safe procedure with low rate of technical failure. The patency of vascular access in long-term was maintained by the repeated intervention. Stent placement could help prolong the patency period for restenosis lesions.